(untitled) (Research, Society and Development, 2020)
Objective: To map the health management of urgent and emergency medical services. Method: This is a scoping review, which used a detailed and individual search strategy for each database: PubMEd, Scopus, Web of Sciece, Cochrane and Virtual Health Library (VHL). Which used as initial eligibility criteria: studies of monitoring and evaluation of the urgency and emergency service, obtaining 9 studies, in which Nvivo software was used for data organization and content analysis. Results: The studies were published between 2007 and 2019, both from national and international territory, so the health management of urgency and emergency units is related to the organizational issues of services (quality of care, process of implementing services – UPA, network management, medical health professionals) and the information systems (evaluation, indicators) that directly contribute to the process. Conclusion: The need to computerize the information of these services, being a fundamental management tool the quality information and in a timely manner for the monitoring and evaluation of health services.